The Effectiveness of Incentive Programs in Enhancing Driver Performance and Retention in the Logistics Sector: A Case of Bollore Logistics Uganda - Josephine Nankunda (Uganda Christian University, 2025)
This study was based on the topic the effectiveness of incentive programs (financial and non- financial incentives) on drivers motivation and retention at Bollore Logistics Uganda. The study was grounded in three objectives: to assess the impact of financial incentives on worker motivation and retention, to examine the effect of non-financial incentives on worker motivation and to assess the effectiveness of Bollore Logistics Uganda's current incentive programs in addressing both hygiene factors and motivators for their drivers. The literature review was uncovers by different scholars who came up with the different ideologies on different retention patterns, a number of motivation schemes and used incentive programs. The literature review was revealed with respect to the stated objectives. A descriptive design was employed and data was obtained through structured questionnaires from 80 company employees, primarily drivers and logistics personnel. Descriptive statistics like frequencies, means, and standard deviations were employed in analyzing the data. The findings indicated that even though monetary rewards also known as financial incentives like performance-based pay, punctual payment, and fair salary were highly rated in general, they were not the sole considerations in keeping the employees with the organization. Non-financial rewards like a safe and pleasant working atmosphere, work-life balance, and acknowledgement received the most consensus of ratings from the respondents. The study concludes that both financial and non-financial incentives must be balanced if the firm is to sustain employee motivation and reduce turnovers. It also recommends that the firm increase promotion opportunities, sustain robust non-financial incentive practices, and reassess incentives on a regular basis in accordance with employee expectations.
Undergraduate